Ceramic Proppants for Hydraulic Fracturing Treatments - T.D. Dzhienalyev, A.A. Biryukova (International Journal of Advanced Science and Technology, 2019)
The results of studies to create magnesium-silicate proppants based on the raw materials of Kazakhstan are presented herein. Serpentinites from chromite ores from the Kempirsai region were used as the main component of the charge. Serpentine as chrysotile and antigorite is the main mineral of serpentinite rock. Impurity minerals of the rock are olivine, carbonates, chromospinelide and hematite. The laws of structural and phase transformations occurring during the heat treatment of serpentinite raw materials in the range of 400-1400°C were studied. It was revealed that the formation of equilibrium phases (forsterite and clinoenstatite) in magnesium silicate ceramics occurs through the formation of metaserpentine, an intermediate metastable compound, which exists at 600-900°C. Magnesium-silicate proppants based on serpentinite with the addition of 10-20% silica sand or refractory clay, were obtained. Proppants were obtained with a bulk density of 1.60-1.65 g/cm3, crush resistance at 34.5 MPa of 10-15%, and roundness and sphericity of 0.8. Properties of the proppants obtained meet the requirements of the API standard.